Knowledge About HPV and the HPV Vaccine: Observational Study on a Convenience Sample of Adolescents from Select Schools in Three Regions in Italy - Laura Brunelli; Francesca Valent; Manola Comar; Barbara Suligoi; Maria Cristina Salfa; Daniele Gianfrilli; Franz Sesti; Giuseppina Capra; Alessandra Casuccio; Erik De Luca; Emily Bertola; Silvia Gazzetta; et al. (Vaccines)
Background/Objectives: HPV is the most common sexually transmitted infectious agent worldwide and adolescents are at high risk of contracting HPV. The aim of our study was to find out how much adolescents know about the virus and its effects, and to obtain information on attitudes and behaviors regarding HPV vaccination to close these gaps. Methods: As part of the ESPRIT project, 598 lower secondary (11–14 years) and upper secondary (14–19 years) school students from three Italian regions were surveyed between December 2023 and March 2024 using a seven-question online questionnaire on awareness, knowledge, and attitudes about HPV and the HPV vaccine. Count and zero-inflation models were used to determine correlations between sexes, urban/suburban, province of residence, and school type with knowledge. Results: Lower secondary students believed that HPV causes HIV/AIDS (8.9%) or hepatitis C (3.0%) and rarely mentioned anal (21%) and oral sex (9.6%) as ways of transmission. Among upper secondary students, misconceptions were similar, with worrying rates of students stating that HPV only causes cancer in females (18%) or males (2.4%), and low rates of identifying transmission risk through anal (41%) and oral (34%) sex and genital contact (38%). The HPV vaccination rate was quite low (47% in lower secondary students, 61% in upper secondary students). In the regressions, sex, urban/suburban area, and province were the variables associated with higher levels of knowledge for lower secondary students; for upper secondary students, level of knowledge was associated with sex, urban/suburban area, school type, and province of residence. Conclusions: Awareness and knowledge of HPV and the HPV vaccine are low among Italian students in this study and reported vaccination coverage is below the national target. Coordinated efforts at the national level are needed to address this public health issue.